Recent advances in nanomaterial-based synergistic combination cancer immunotherapy - Sang, Wei; Zhang, Zhan; Dai, Yunlu; Chen, Xiaoyuan (Chemical Society reviews, 2019)
In recent years, conventional treatments including surgery, chemotherapy and radiotherapy have been the main approaches in tumour therapy. Cancer immunotherapy is a new therapeutic modality to fight cancer by harnessing the power of patients' own immune system. Ongoing research related to these therapies has demonstrated their advantages and intrinsic limitations. Nanomaterial-based platforms are utilized in these emerging fields. In particular, a combination of other treatment methods with cancer immunotherapy to achieve precision medicine and prevent recurrence and metastasis, could improve patients' outcome. The combined multiple treatments have superior efficacy to any monotherapy alone in producing improved anti-cancer activity. Therefore, it's necessary to summarise research advances in nanomaterial-based combination cancer immunotherapy contributing to clinical transformation. This review is based on the principles of cancer immunotherapy and the combined treatment design reflected by advances in materials science, including the structures of nanoplatforms and their underlying mechanisms towards cancer. The ultimate goals are to stimulate the design of better strategies for versatile use in the future based on biomaterial engineering methods to enhance the efficacy of combined cancer treatments, and to provide new ideas for the prospects of a synergistic cancer combination immunotherapy for clinical application transformation. This review aims to summarize various synergistic combination cancer immunotherapy strategies based on nanomaterials.